CGS-BASED NONVOLATILE MEMORY PROGRAMMING SPEED - Slobodian, Ivan (Scientific Works of Vinnytsia National Technical University, 2015)
The paper studies the influence of a set of factors on the speed of programming the nonvolatile memory (NVM) based on chalcogenide glassy semiconductor (CGS). The method is described for determining the speed of programming the device switching on (crystallization, low-resistance state) and switching it off (amorphization, high-resistance state). It is also shown that the speed of switching off and on the NVM depends mainly on the electric contact of the device. REFERENCES 1. Ovshinsky S. R. Reversible electrical switching phenomena in disordered structures / S. R. Ovshinsky // Physical Review Letters. – 1968. – № 21. – P. 1450 – 1453. 2. Phase Change Memory / H.-S. Philip Wong [et al.] // Proceedings of the IEEE. – 2010. – Vol. 98, №. 12. – P. 2201 – 2227. 3. Phase change memory technology [Електронний ресурс] / Bipin Rajendran [et al.] / IBM Research. – 2009. Режим доступу: http://www.itrs.net/ITWG/Beyond_CMOS/2010Memory_April/Proponent/Nanowire%20PCRAM.pdf. 4. Костылев С. Электронное переключение в аморфных полупроводниках / С. Костылев, В. Шкут. – Наукова думка: Київ, 1978. – с. 203.